The PENGARUH E-WOM DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK HANASUI MAHASISWA IAIN KENDARI - lestari daswan; Tri Desi Lestari; Fauzan Fauzan; Markoni Markoni; Hartini Hartini (Jurnal Manajemen dan Kewirausahaan, 2024)
The purpose of this research is to determine (1) The influence of electronic word of mouth (e-WOM) on the decision to purchase Hanasui cosmetic products among IAIN Kendari students, (2) The influence of price on the decision to purchase Hanasui cosmetic products among IAIN Kendari students, (3) The influence of electronic word of mouth (e-WOM) and price on purchasing decisions for Hanasui cosmetic products among IAIN Kendari students. This research uses a purposive sampling technique. The sample in this study was 75 respondents. The data analysis technique uses multiple linear regression analysis. The results of this research show that e-WOM influences the decision to purchase Hanasui cosmetic products among IAIN Kendari students, price influences the decision to purchase Hanasui cosmetic products among IAIN Kendari students, e-WOM and product price influence the decision to purchase Hanasui cosmetic products among IAIN students Kendari.